Cross language priming extends to formulaic units: evidence from eye-tracking suggests that this idea “has legs” - Carrol, Gareth; Conklin, Kathy (Cambridge University Press, 2017)
Idiom priming effects (faster processing compared to novel phrases) are generally robust in native speakers but not non-native speakers. This leads to the question of how idioms and other multiword units are represented and accessed in a first (L1) and second language (L2). We address this by investigating the processing of translated Chinese idioms to determine whether known L1 combinations show idiom priming effects in non-native speakers when encountered in the L2. In two eye-tracking experiments we compared reading times for idioms vs. control phrases (Experiment 1) and for figurative vs. literal uses of idioms (Experiment 2). Native speakers of Chinese showed recognition of the L1 form in the L2, but figurative meanings were read more slowly than literal meanings, suggesting that the non-compositional nature of idioms makes them problematic in a non-native language. We discuss the results as they relate to crosslinguistic priming at the multiword level.